Feasibility Study of Production of Double Blade Grass Cutting Machine - C. Bagaihing, Ery; Mangesa, Daud Pulo; Bale, Jefri S. (Garuda Prestasi Nusantara Consulting, 2022)
Most breeders generally feed their livestock only with grass, but for the grass itself it will be food that is easily found and is mostly given to livestock. However, most people still use machetes or sickles to cultivate grass, therefore SMEs have emerged in dealing with grass processing. The tool made is a grass chopper machine, the machine that was created also has several variations, one of which is a double knife chopper machine made by one of the students of the Nusa Cendana University Kupang, namely Stenly Naitboho. Therefore, this research was conducted to assess the performance of the chopper machine based on a feasibility study, in terms of the percentage length of the chopped material and the consumption of fuel used along with the production costs of this tool. In completing this research, several methods are needed to launch it, namely literature study and observation. After using the method used, the results of the chopping can be found, namely the percentage of the length of the chopped material measuring < 5 cm (W1) obtained an average of 54.62%, while the average percentage of the length of the chopped material measuring > 5 cm (W2) is 45.28%. For the size of the good chopped results is 2-5 cm in accordance with SNI 7785.1:2003 concerning the requirements for the results of the forage chopping machine. Another result in this study is the consumption of fuel used during the census obtained an average of 0.6 /hour. Based on SNI 7580:2013 the requirements for chopper work for fuel consumption of this machine are in category A. Production costs are obtained at a price of Rp. 4,122,200/ unit. Keywords:Consumption, Fuel, Shredded, Production